The effectiveness of physical activity interventions on blood pressure in children and adolescents: A systematic review and network meta-analysis - Mohamed A. Hassan; Wanjiang Zhou; Mingyi Ye; Hui He; Zan Gao (Elsevier, 2024)
Background: High blood pressure (BP) is a major contributor to mortality and cardiovascular diseases. Despite the known benefits of exercise for reducing BP, it is crucial to identify the most effective physical activity (PA) intervention. This systematic review and network meta-analysis (NMA) aimed to evaluate the available evidence on the effectiveness of various PA interventions for reducing BP and to determine their hierarchy based on their impact on BP. Methods: A search of PubMed, SPORTDiscus, PsycINFO, Web of Science, CINAHL, Cochrane, and Eric databases was conducted up to December 2022 for this systematic review and NMA. Randomized controlled trials and quasi-experimental studies targeting healthy children and adolescents aged 6-12 years old were included in this study. Only studies that compared controlled and intervention groups using PA or exercise as the major influence were included. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Three independent investigators performed the literature screening, data extraction, and risk of bias assessment. We used Bayesian arm-based NMA to synthesize the data. The primary outcomes were systolic BP and diastolic BP. We calculated the mean differences (MDs) in systolic BP and diastolic BP before and after treatment. Mean treatment differences were estimated using NMA and random-effect models. Results: We synthesized 27 studies involving 15,220 children and adolescents. PA combined with nutrition and behavior change was the most effective intervention for reducing both systolic BP and diastolic BP (MD = -8.64, 95% credible interval (95%CI):-11.44 to -5.84; MD = -6.75, 95%CI: -10.44 to -3.11), followed by interventions with multiple components (MD = -1.39, 95%CI: -1.94 to -0.84; MD = -2.54, 95%CI: -4.89 to -0.29). Conclusion: Our findings suggest that PA interventions incorporating nutrition and behavior change, followed by interventions with multiple components, are most effective for reducing both systolic BP and diastolic BP in children and adolescents.